2013
DOI: 10.1093/heapol/czt015
|View full text |Cite
|
Sign up to set email alerts
|

With the help of a foreign ally: biopharmaceutical innovation in India after TRIPS

Abstract: This article investigates the implications of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), which reached full-fledged implementation in 2005, for the patenting activity of Indian biopharmaceutical companies. The Indian biopharmaceutical industry is well-known for its generic producers, whose business models capitalize on the opportunity to reverse-engineer patented compounds and produce them at low costs through process innovation. By strengthening intellectual property right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The TRIPS Agreement created an environment legitimizing innovators and generic companies, stimulating cross-border alliances, increasing numbers of R&D alliances, patent filings, and R&D investment. The main issue remains the impact of TRIPS on drug pricing and on biopharmaceutical companies’ willingness to invest in health problems at the local level ( 28 ).…”
Section: Ip As a Tool To Facilitate Access To Medicinesmentioning
confidence: 99%
“…The TRIPS Agreement created an environment legitimizing innovators and generic companies, stimulating cross-border alliances, increasing numbers of R&D alliances, patent filings, and R&D investment. The main issue remains the impact of TRIPS on drug pricing and on biopharmaceutical companies’ willingness to invest in health problems at the local level ( 28 ).…”
Section: Ip As a Tool To Facilitate Access To Medicinesmentioning
confidence: 99%
“…Girma et al (2009) These are active monitoring, eliminating innovation failures, and facilitating technology transfers from innovative countries to non-innovators. Angeli (2014) examining 123 Indian biopharmaceutical firms between 1999 and 2009, have found that firms with foreign partners became more successfull at implementing innovation activities. Bertschek (1995) found that foreign direct investment through technology transfer from foreign investors to domestic firms, facilitates process innovations.…”
Section: Figure 2 Factor Loadings Of Product Oriented Impact Versus mentioning
confidence: 99%
“…In comparison, patented medicines in the US market cost on average three times as much as the subsequently marketed generic drug [38]. In addition, one study even suggests that it was India's obligation to comply with TRIPS that transformed several companies' business models from imitation-based to innovation-based [39].…”
Section: Patents and Access To Medicinesmentioning
confidence: 99%